1987
DOI: 10.1111/j.1365-2125.1987.tb03191.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nedocromil on weal reactions in human skin.

Abstract: 1 Nedocromil 2% iontophoresed into human skin had no effect on wealing produced by intradermal histamine, 48/80 or house dust mite antigen. 2 Iontophoresis of 0.002-2% nedocromil itself resulted in dose-related wealing.3 This wealing was reduced by 62 ± 8% s.e. mean by the Hl-receptor antagonist terfenadine which decreased histamine wealing by 68 ± 2% s.e. mean. 4 Nedocromil may therefore act as a weak agonist on a skin mast cell receptor concerned with histamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Also, the drug did not inhibit the weal response as would have been expected if it had antihistaminic effects. Indeed, with the higher concentration of histamine, there was a statistically significant increase in the area of the weal, an observation similar to that previously reported ( Humphreys et al ., 1987 ).…”
Section: Discussionsupporting
confidence: 91%
“…Also, the drug did not inhibit the weal response as would have been expected if it had antihistaminic effects. Indeed, with the higher concentration of histamine, there was a statistically significant increase in the area of the weal, an observation similar to that previously reported ( Humphreys et al ., 1987 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nedo also has no effect on mediator release from skin mast cells. This failure to inhibit IgE-dependeni mediator release supports the findings of Humphreys and Shuster [24] that this drug iontophoresed into human skin had no effect on wealing produced by intradermal histamine, 48/80 or house dust mite antigen. This failure clearly distinguishes human skin mast cells from the other mast cells examined.…”
Section: Discussionsupporting
confidence: 86%
“…Following astemizole treatment, HUMPHREYS et al (1987) found a 47% inhibition ofwealing with house dust mite and 68% inhibition of compound 48/80 wealing while histamine wealing was inhibited by 83%; these observations might imply that while histamine has a role in mediating the weal and flare reaction, other mediators are also involved, as suggested by KRAUSE and SHUSTER (1984). However, HUMPHREYS et al (1987) showed that topical indomethacin did not affect the rate of formation, the magnitude, or the rate of disappearance of weals induced by histamine, compound 48/80, or house dust mite extract. Indomethacin has been said to attenuate the late skin response with allergen challenge, implying that cyclo-oxygenase products of arachidonic acid, possibly prostaglandin D 2 , are important in this response also (GRONNENBERG and ZETTER-STROM 1985).…”
Section: G Pharmacological Modulation Of Mediator Secretion From Skimentioning
confidence: 71%
“…In chopped human skin, P2-agonists are at least 100 times less efficacious in inhibiting IgE-dependent histamine secretion compared with their effects on dispersed lung mast cells (CLEGG et al 1985), supporting the findings in vivo. Furthermore the more recently introduced sodium nedecromil, which inhibits release from lung mast cells, causes histamine release in skin (HUMPHREYS and SHUSTER 1987). This chromone has a potent activity in inhibiting mediator secretion from isolated rat peritoneal mast cells (ORR 1975), though it is less active on histamine secretion from either chopped human lung fragments (CHURCH and YOUNG 1983) of dispersed human lung mast cells (CHURCH and HIROI 1987).…”
Section: G Pharmacological Modulation Of Mediator Secretion From Skimentioning
confidence: 99%